2017
DOI: 10.1063/1.5000972
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of mode-2 internal solitary wave over a pseudo slope-shelf

Abstract: Numerical simulations are performed to investigate the effect of wave amplitude in a numerical wave tank on the evolution of a convex mode-2 internal solitary wave (ISW) propagating over a pseudo slope-shelf. A finite volume method based on a Cartesian grid system is adopted to solve the Navier-Stokes equations using Improved Delayed Detached Eddy Simulation model for the turbulent closure. Numerical results reveal three types of waveform during wave generation on the flat bottom: (1) pseudo vortex shedding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This finding adds particular relevance to comparisons of the shoaling behaviours observed by Cheng et al (2017) for the slope-shelf topography with those reported herein for constant slope cases (without a shelf). Cheng et al (2017) considered the same undisturbed, stable density configuration as the present paper, namely two homogeneous layers of different density but equal thickness, separated by a thin pycnocline. The mid-level of the undisturbed pycnocline was prescribed to be always above the plateau section of the slope-shelf topography and a single slope with a fixed length and angle θ (θ = 6 • ; s = tan θ = 0.105) was considered.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…This finding adds particular relevance to comparisons of the shoaling behaviours observed by Cheng et al (2017) for the slope-shelf topography with those reported herein for constant slope cases (without a shelf). Cheng et al (2017) considered the same undisturbed, stable density configuration as the present paper, namely two homogeneous layers of different density but equal thickness, separated by a thin pycnocline. The mid-level of the undisturbed pycnocline was prescribed to be always above the plateau section of the slope-shelf topography and a single slope with a fixed length and angle θ (θ = 6 • ; s = tan θ = 0.105) was considered.…”
Section: Introductionsupporting
confidence: 75%
“…Test runs conducted by Cheng et al (2017) to replicate the laboratory study by Carr et al (2015) for constant depth conditions showed excellent agreement between numerical simulations and laboratory data. This finding adds particular relevance to comparisons of the shoaling behaviours observed by Cheng et al (2017) for the slope-shelf topography with those reported herein for constant slope cases (without a shelf). Cheng et al (2017) considered the same undisturbed, stable density configuration as the present paper, namely two homogeneous layers of different density but equal thickness, separated by a thin pycnocline.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations